Relavansi Tradisi Ngabuburit terhadap Literasi Ekonomi Konsumtif dan Etika Konsumsi Islam pada Mahasiswa Bandung (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Ngabuburit has grown into a cultural tradition that is deeply embedded in Indonesian society during Ramadan, including among the student demographic. This study investigates the relevance of the ngabuburit tradition to the level of consumer economic literacy and the application of Islamic consumption ethics among university students in the city of Bandung. Employing a quantitative descriptive approach, data were gathered through an online questionnaire distributed to students from various universities across Bandung. The analysis aims to determine whether the pre-iftar waiting activity stimulates impulsive purchasing behavior more strongly than awareness of Islamic consumption principles particularly the avoidance of wasteful spending (tabzir) and extravagance (israf). The study also examines several factors shaping students' consumption patterns, including social environment, lifestyle tendencies, and access to food and beverage products throughout Ramadan. The results are expected to shed light on how students behave as consumers within a local cultural framework and to what degree their economic literacy can moderate consumption behaviors that contradict Islamic principles, while providing an evaluative foundation for cultivating more prudent consumption habits.